2015
DOI: 10.1007/s10457-015-9826-6
|View full text |Cite
|
Sign up to set email alerts
|

Does participatory forest management program lead to efficient forest resource use and improved rural livelihoods? Experiences from Mua-Livulezi Forest Reserve, Malawi

Abstract: This study evaluates the efficacy of Improved Forest Management for Sustainable Livelihoods Program (IFMSLP) in communities adjacent to Mua-Livulezi Forest Reserve, Malawi. The program is specifically aimed at alleviating poverty and enhance rural livelihoods through promoting greater community involvement in forest management while providing access and associated benefits. The study therefore evaluated the effect of the program on community organisation, forest access, forest use, product availability and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…The observed permitted and non-permitted forest uses were also noted by Vatn et al (2013) in the same study area and by Senganimalunje et al (2015) in other conservation initiatives in Malawi. This further indicates that this strategy might be a good way of limiting forest use and achieve sustainable forest management and conservation under the REDD+ initiative.…”
Section: Community Perceptions On the Use Of Forests Before And Aftersupporting
confidence: 87%
See 1 more Smart Citation
“…The observed permitted and non-permitted forest uses were also noted by Vatn et al (2013) in the same study area and by Senganimalunje et al (2015) in other conservation initiatives in Malawi. This further indicates that this strategy might be a good way of limiting forest use and achieve sustainable forest management and conservation under the REDD+ initiative.…”
Section: Community Perceptions On the Use Of Forests Before And Aftersupporting
confidence: 87%
“…As noted earlier, REDD+'s regulation of access to forests means that the forests are utilized based on the management plan. According to Senganimalunje, Chirwa, Babalola and Graham (2015), access to forest products could mean that the community are provided with various livelihood resources. However, they further noted that regulated access to forests resulted in negative 21 social changes to the community.…”
Section: Community Perceptions On the Use Of Forests Before And Aftermentioning
confidence: 99%
“…Collective action for the natural resource management shapes by individuals and its transformations within groups and individuals. It holds the greatest promise for the collective and sustainable governance of natural resources (Meilasari and Sugiana 2012) and individuals who can mitigate negative outcomes resulted from resource use that livelihoods depend on (Senganimalunje et al 2016). Agroforestry is intended to be an alternative for sustainable forest management, unfortunately collective action on developing agroforestry practices in both villages is still weak.…”
Section: Trust and Collective Action In Agroforestry Developmentmentioning
confidence: 99%
“…A study in Nepal [62] also indicated a similar tendency for men participation in forest protection. Furthermore, women mostly rely on various small products from the forest to support their livelihoods [87,88].…”
Section: Variables Economic Benefits Meetings Protectionmentioning
confidence: 99%